Control of Exchange Interactions in π Dimers of 6‐Oxophenalenoxyl Neutral π Radicals: Spin‐Density Distributions and Multicentered–Two‐Electron Bonding Governed by Topological Symmetry and Substitution at the 8‐Position. Issue 36 (6th August 2013) - Nishida, Shinsuke; Kawai, Junya; Moriguchi, Miki; Ohba, Tomohiro; Haneda, Naoki; Fukui, Kozo; Fuyuhiro, Akira; Shiomi, Daisuke; Sato, Kazunobu; Takui, Takeji; Nakasuji, Kazuhiro; Morita, Yasushi
Abstract The tri‐tert‐butylphenalenyl (TBPLY) radical exists as a π dimer in the crystal form with perfect overlapping of the singly occupied molecular orbitals (SOMOs) causing strong antiferromagnetic exchange interactions. 2, 5‐Di‐tert‐butyl‐6‐oxophenalenoxyl (6OPO) is a phenalenyl‐based air‐stable neutral π radical with extensive spin delocalization and is a counter analogue of phenalenyl in terms of the topological symmetry of the spin density distribution. X‐ray crystal structure analyses showed that 8‐tert‐butyl‐ and 8‐(p‐XC6H4)‐6OPOs (X=I, Br) also form π dimers in the crystalline state. The π‐dimeric structure of 8‐tert‐butyl‐6OPO is seemingly similar to that of TBPLY even though its SOMO–SOMO overlap is small compared with that of TBPLY. The 8‐(p‐XC6H4) derivatives form slipped stacking π dimers in which the SOMO–SOMO overlaps are greater than in 8‐tert‐butyl‐6OPO, but still smaller than in TBPLY. The solid‐state electronic spectra of the 6OPO derivatives show much weaker intradimer charge‐transfer bands, and SQUID measurements for 8‐(p‐BrC6H4)‐6OPO show a weak antiferromagnetic exchange interaction in the π dimer. These results demonstrate that the control of the spin distribution patterns of the phenalenyl skeleton switches the mode of exchange interaction within the phenalenyl‐based π dimer. The formation of the relevant multicenter–two‐electron bonds is discussed.